Effect of drying technologies on the biochemical properties of Stolephorus commersonnii. Issue 3 (7th July 2018) - Patterson, Jamila; Kailasam, Saritha; Giftson, Hermina; Immaculate, Jeyasanta K
Abstract: Objectives: Two different methods, namely traditional sundrying and solar dryer drying were employed to investigate the effect of drying method on the quality of Indian anchovies, Stolephorus commersonnii. Materials and Methods: Fifty fish samples of Stolephorus commersonnii were purchased for the drying study. Traditionally dried fishes were bought from the local market. For solar drying the samples were kept in on the solar cabinet dryer KSD 25 designed and fabricated by the Central Institute of Fisheries Technology (CIFT). International standard AOAC methods were used for quality analysis of dried fish samples. Results: The method of drying by the solar dryer is more hygienic and faster than the traditional sun-drying method. The biochemical compositions and sensory evaluation of the products obtained showed significant variation between the two drying methods. Solar dryer–dried fish has got good organoleptic score than the traditional sundried fish. The overall quality of fish dried in the solar dryer was better than the traditionally sundried fish. Conclusions: The study clearly indicates that solar drying can be used as an environment-friendly method for fish processing which enhances food security.